EVALUATION OF THE BONE SUPPLY NECESSARY FOR IMPLANT INSERTION USING THE CBCT TECHNIQUE - PROSPECTIVE STUDY - Sorana Maria Bucur; Dorin Ioan Cocoș; Radu Mircea Sireteanu Cucui; Smaranda Nazarie (Romanian Society of Oral Rehabilitation, 2021)
Aim of the study: Implant surgery and implant prosthesis have become the ideal solution for replacing missing teeth. For the success of the implants, it is essential to determine the quality and quantity of the host bone, the most indicated means of investigation being dental cone-beam computed tomography (CBCT). Material and method: Our study was performed on 100 adult patients with a mean age of 48.5±23.5. We determined the frequency of edentations depending on age and patients' sex. Dental CBCTs were used to determine the bone height, width, density, and the dimension of eventually present concavity of the buccal cortical bone. We used Pearson coefficients for correlations between the bone height and density, respectively bone width, and density. Results: The results showed that most of the patients in need of dental implants are men and the frequency of edentations increases with age. Between 20% and 44% of patients have the concavity of buccal plate with the deep of 1 mm. The predominant bone density type was D3 in frontal maxilla and lateral mandible, D2 in frontal mandible, and D4 in lateral maxilla. The maximum bone heigh was in the frontal maxilla (13.0±2.2 mm) and the maximum bone width was in the lateral mandible (8.7±3.6). We found weak positive correlations between the bone height and bone density in the anterior maxilla (r=0.256, p=0.042) and anterior mandible (r=0.204, p=0.048), and between the bone width and bone density in the anterior maxilla (r=0.308, p=0.046) but no other positive correlations were found. Conclusions: as far as we cannot determine strong correlations between the bone dimensions and bone density, CBCT appears to be the only tool we have to determine the real bone offer for dental implants.